Realizing local development in the carbon commodity chain: Political economy, value and connecting carbon commodities at multiple scales - Adam Bumpus (United Nations Research Institute for Social Development (UNRISD), 2011)
This paper provides an analysis of how local community development is connected to the global carbon economy through the creation of carbon commodities (offset credits) and the role of premium credit certification in assisting in local development. The paper shows that information on local conditions should be focused on political-economic processes and the interactions between actors to nuance the social benefits of carbon credit generation in developing country contexts. International carbon finance markets are seen as tools to reduce global emissions at lowest cost and contribute to sustainable development in developing countries. Carbon finance can potentially create lasting development benefits, including the transition to-and scaling up of-low carbon sustainable economies that are pro-poor. However, the social benefits of carbon finance have so far been unevenly distributed. Carbon markets that are focused solely on carbon reductions tend to obscure local social development contexts. In order to redress these imbalances, pro-development carbon funds and standards to certify projects with local benefits have been created to help place a price on local social dimensions of projects. This paper, however, shows that although such premium carbon 'Premium' carbon relates to the inclusion of certain carbon offset projects into standards, such as the Gold Standard (www.cdmgoldstandard.org), which aim to certify and communicate the social benefits of projects to buyers. certification may increase global carbon credit prices, it does not necessarily improve local conditions. Therefore, premium carbon should be seen within broader contexts: projects are 'wired in' and connected through multiscalar political-economic structures that create both opportunities and constraints for local development within and outside of pro-development labels and funds; global carbon finance influences do not flow unidirectionally: local agency interacts with global structures of carbon finance, reworking it in local contexts and shifting the value placed on credits at global levels; and the communication and 'unveiling' of local production of the carbon commodity does not necessarily change local outcomes, but provides some movement to include social dimensions in a more structured way...
Keywords: 330